Effect of Discrete Levels Width Error on the Optical Performance of the Diffractive Binary Lens - Manal Alshami; Mohamed Fawaz Mousselly; Anas Wabby (International Journal of Optics)
The effects of discrete levels width error developed by thin film deposition on the optical performance of diffractive binary germanium lens with four discrete levels are investigated using nonsequential mode in the optical design code ZEMAX. The thin film deposition technique errors considered are metallic mask fabrication errors. The peak value of the Point Spread Function (PSF) was used as criterion to show the effect of discrete levels width error on the optical performance of the four-level binary germanium lens.